Is higher serum cholesterol associated with altered tendon structure or tendon pain? A systematic review. Issue 23 (15th October 2015) - Tilley, Benjamin J; Cook, Jill L; Docking, Sean I; Gaida, James E
Abstract : Background: Tendon pain occurs in individuals with extreme cholesterol levels (familial hypercholesterolaemia). It is unclear whether the association with tendon pain is strong with less extreme elevations of cholesterol. Objective: To determine whether lipid levels are associated with abnormal tendon structure or the presence of tendon pain. Methods: We conducted a systematic review and meta-analysis. Relevant articles were found through an electronic search of 6 medical databases—MEDLINE, Cochrane, AMED, EMBASE, Web of Science and Scopus. We included all case–control or cross-sectional studies with data describing (1) lipid levels or use of lipid-lowering drugs and (2) tendon structure or tendon pain. Results: 17 studies (2612 participants) were eligible for inclusion in the review. People with altered tendon structure or tendon pain had significantly higher total cholesterol, low-density lipoprotein cholesterol and triglycerides, as well as lower high-density lipoprotein cholesterol; with mean difference values of 0.66, 1.00, 0.33, and −0.19 mmol/L, respectively. Conclusions: The results of this review indicate that a relationship exists between an individual's lipid profile and tendon health. However, further longitudinal studies are required to determine whether a cause and effect relationship exists between tendon structure and lipid levels. This could lead to advancement in the understanding of the pathoaetiology and thus treatment of tendinopathy.